STUDYING THE PROCESS OF OBTAINING LIQUID FERTILIZER WITH PHYSIOLOGICAL ACTIVITY (Academicia Globe: Inderscience Research, 2022)
In the work to justify the process of obtaining liquid fertilizers based on solutions of potassium sulfate, ammonium nitrate, carbamide, copper sulfates and monoethanolammonium. The dependence of changes in the physicochemical properties of solutions on the composition of the components has been studied. On the basis of the data obtained, the “composition-property” diagrams were constructed.